Vietnam Primary School Students’ Ability of Applying Mathematics Knowledge into Real Life - nguyen, chau huu; Le thi, Huong Thu (Advances in Social Sciences Research Journal, 2018)
Mathematics is closely related to reality and widely applied in many different fields of science, technology as well as in real life. With its special role, Mathematics is essential for all sciences, contributing to an increasingly modern and civilized social life. This paper presents a study of the arrangement of practical elements in Mathematics textbooks and the analysis of primary school students’ abilities in applying Mathematics knowledge into practice. This research also aims to emphasize the importance of developing students’ mathematical application competencies in teaching and learning mathematic in primary schools and the need to change teachers’ perceptions and actions through some recommendations accordingly.